Caesarean section in the opinion of pregnant women - Sienkiewicz, Anna; Kulesza-Brończyk, Bożena; Piekut, Krystyna; Dobrzycka, Bożena; Terlikowski, Sławomir Jerzy (Polish Journal of Public Health, 2009)
Objective. The aim of this study was to analyze factors motivating future mothers to terminate their pregnancy by means of caesarean section and to specify the percentage of such mothers in Bialystok city. Material and method. The survey was conducted among 132 pregnant women, patients of Bialystok hospitals, clinics and participants of school of birth. Results. The results of the survey indicate a high interest in the caesarean section. Over 21% respondents would opt for this method of termination of pregnancy. A high proportion of respondents (70%) regard caesarean section as “trendy”. Respondents’ knowledge about pregnancy and labour stems mainly from magazines. This form of information source was stated by 78% of respondents. The highest percentage of caesarean section enthusiasts (23%) is among women for whom the doctor is the source of knowledge. The most important factor inclining women to make a decision about undergoing caesarean section is the fear of pain (56%). Conclusions. The low level of medical knowledge underlies the interest in caesarean section as a means of delivery and increases the belief that surgical intervention is safer and less prone to complications than natural childbirth.